Developing And Standardizing A Catastrophic Thinking Scale For Staff In Physical Education And Sports Science Colleges - M. M. Maytham Muzal Bahidh, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study aimed to develop and standardize a catastrophic thinking scale for employees in colleges of physical education and sports sciences.Materials and Methods. A descriptive survey design was used. The population comprised 180 employees. Participants were selected purposively: 100 employees for scale development, 10 for a pilot test, and 70 for standardization (total sample = 52.396% of the population). Data were collected by administering the developed scale across these stages to support the standardization process.Results. The scale items and themes were clear and relevant to employee work-related issues. Findings indicated that continuous work pressures may contribute to fragmented catastrophic thinking. Overall, the scale demonstrated the capacity to measure catastrophic thinking among employees in a broader and more comprehensive way than previously assumed. The results also emphasized the need for greater attention to employee well-being, as occupational stress can foster catastrophic and unbalanced thinking that may affect work performance.Conclusions. The catastrophic thinking scale is ready for use in assessing employees in physical education and sports sciences colleges. Regular monitoring and periodic studies are recommended to better understand catastrophic thinking and support employee well-being. Future research should apply the scale to different samples to strengthen its usefulness and expand evidence for its implementation.